Understanding Social Media Adoption: The Role Of Perceived Media Needs And Technology Characteristics - Zolkepli, I.A.; Kamarulzaman, Y. (Zia World Press, Australia, Australia, 2011)
Evidence suggests that consumer’s needs for traditional media constitutes an essential determinant in consumer media adoption. However, studies on the need for non-traditional media still remain scarce. It continues to be questionable whether consumer media needs would have the same significant impact on social media, since its nature is highly interactive and user controlled. Drawing upon the Uses and Gratification Theory and Diffusion of Innovation Theory, this paper aims to understand the adoption of social media among Internet users. A proposed model is developed by integrating the dimensions of consumer perceived media needs and perceived characteristics of social media technology as the drivers for adoption behaviour. The model will be able to better enhance the understanding of researchers and practitioners of consumer predictive needs and their relationship to the speed of consumer adoption behaviour in social media.